Librarian and Traditional Knowledge : A Study Of Urgency and The Role Of Librarian In Traditional Knowledge - Adelia, Nisa (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
Indonesia is an island country which is rich of cultural treasure. These cultural treasure are including moral value, Knowledge and technology that is used by hereditary from local tradition. Most of these hereditary habits are done by oral tradition, so it less of documentations. Library as information center and has function to serve information, willy nilly, librarian has responsibility to preserve the knowledge of traditional culture as intellectual property. Besides of that, the documentation activity will become cultural defense of indonesia so, it can be used by the next generation for learning activity. View the significant of cultural documentation activity, in this paper want to discussion about role of librarian in traditional knowledge. This type of research is study literature research. We will use a variety of literature that discusses traditional knowledge. Then do the assessmentÂ about of the role of librarians to traditional knowledge